The Chairperson : Faculty, Administrator and Academic and Crisis Leader - Domenick J Pinto (Academic Chairpersons Conference Proceedings, 2023)
For 36 years, I have witnessed the evolution of the role of chair as economic, social and student climates emerge. My workshop will summarize the challenges that chairs must now face in 2023. The session will help relatively new and new chairs observe various scenarios and discuss how to problem solve them.
Keywords: conflict; management. challenges; change; economy